Problem Based Learning Model Assisted by Kahoot Media and its Role in Enhancing Student Learning Outcomes in Pancasila Education at Grade V Elementary School - Nurul Patwa; Desyandri Desyandri; Reinita Reinita; Zuryanty Zuryanty (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine the effect of the Problem Based Learning (PBL) model assisted by Kahoot media on the learning outcomes of Grade V elementary school students in Pancasila Education at Kecamatan Guguak, Kabupaten Lima Puluh Kota, West Sumatra. Methodology: A quasi-experimental method was employed using a nonequivalent control group pretest-posttest design. The experimental group (n = 12) received PBL instruction integrated with Kahoot media across two learning sessions, while the control group (n = 15) underwent conventional instruction. Data were collected using a validated 15-item multiple-choice cognitive test and analyzed using the Liliefors normality test, Fisher homogeneity test, and independent samples t-test (α = 0.05). Main Findings: The experimental class achieved a posttest mean of 86.67 (gain = +28.89), significantly higher than the control class mean of 71.56 (gain = +17.34). The independent samples t-test yielded t-hitung = 3.524 > t-tabel = 2.060 (df = 25, p = 0.002 < 0.05), confirming that the PBL model assisted by Kahoot exerts a significant positive effect on student learning outcomes compared to conventional instruction. Novelty/Originality of this study: This study offers a novel empirical contribution by integrating the PBL instructional model with the Kahoot gamification platform specifically within Pancasila Education at the elementary level in the Indonesian regional context of Lima Puluh Kota Regency. Unlike prior studies examining PBL or Kahoot independently, this research provides rigorous quasi-experimental evidence of their combined synergistic effect on student achievement.